Oncolytic parvoviruses as tools for cancer gene therapy - Raykov, Zahari Zahariev; Rommelaere, Jean (Biotechnology & biotechnological equipment, 2014)
Gene therapy of cancer by means of recombinant viruses (vectors) that express transgenes and specifically kill neoplastically transformed cells (oncolysis) is a novel approach in the treatment of this lethal disease. Autonomous parvoviruses have been shown to preferentially replicate in and kill in vitro-transformed cells. Reduction of the incidence of spontaneous and implanted tumors in animals by means of parvoviruses is seen in numerous models, including also human neoplasias in immunodeficient mice. However, these agents in their wild type form are often not potent enough to kill all tumor cells equally well. With the aim of enhancing the intrinsic antitumor effect and the range of natural parvoviruses, recombinant parvovirus vectors were constructed expressing various cytotoxic, immunostimulating and antiangiogenie transgene products. These vectors proved to be quite safe and efficient in different anticancer protocols. In summary, due to their natural oncotropic and oncolytic properties, combined with absent pathogenicity, certain members of parvoviruses present an attractive tool in the fight against cancer.
Elektronische Reproduktion der Druckausgabe
Gesehen am 19.02.2021